2020
DOI: 10.1002/pd.5622
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal imaging features and postnatal outcomes of isolated fetal duplex renal collecting system: A systematic review and meta‐analysis

Abstract: Objectives To perform a systematic review of studies reporting the outcome of fetuses with a prenatal diagnosis of isolated duplex collecting system (DCS). Methods Inclusion criteria were studies reporting the outcome of fetuses with a prenatal diagnosis of isolated DCS, defined as DCS not associated with other major structural anomalies at the time of diagnosis. The outcomes observed were: imaging features of DCS on prenatal ultrasound, associated anomalies detected exclusively at prenatal follow‐up ultrasoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…One (1%) female child in our cohort was diagnosed with vesicoureteral reflux and recurrent UTIs, a rate similar to that of the general population and in agreement with other studies that reported a low rate of urinary vesicoureteral reflux complicated by UTIs among children [18][19][20][21][22]. Interestingly, a meta-analysis, which included 11 studies with 284 fetuses who were diagnosed with isolated DCS [23], reported a significant proportion of vesicoureteral reflux and urinary tract infections postnatally. However, renal pelvis dilatation was present in many cases, and 41% of the fetuses had worsening pelvic/ureteric dilatation over the course of the pregnancy, which could affect the outcome.…”
Section: Discussionsupporting
confidence: 91%
“…One (1%) female child in our cohort was diagnosed with vesicoureteral reflux and recurrent UTIs, a rate similar to that of the general population and in agreement with other studies that reported a low rate of urinary vesicoureteral reflux complicated by UTIs among children [18][19][20][21][22]. Interestingly, a meta-analysis, which included 11 studies with 284 fetuses who were diagnosed with isolated DCS [23], reported a significant proportion of vesicoureteral reflux and urinary tract infections postnatally. However, renal pelvis dilatation was present in many cases, and 41% of the fetuses had worsening pelvic/ureteric dilatation over the course of the pregnancy, which could affect the outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Most of the urinary congenital abnormalities are diagnosed with antenatal USG, one of which is duplex system anomalies. Many studies in the literature show that approximately 70% of patients diagnosed with the prenatal duplex system are associated with ureterocele [6]. The presence of a duplex system presents questions surrounding VUR.…”
Section: Discussionmentioning
confidence: 99%
“…DCS is one of the most common congenital anomalies of the urinary tract (UT), accounting for 0.7-1% of all anomalies [4]. It is characterized by a duplex kidney, where every unit acts as a separate pelvicalyceal system that finally drains into the bladder via either a complete or an incomplete collecting system.…”
Section: Introductionmentioning
confidence: 99%